(untitled) (International Journal of Medical and Surgical Sciences, 2023)
The relationship between nutrition and immunity is very complex, because each phase of the immune response can be affected by the lack of essential nutrients such as vitamins and minerals. In addition, it has been described that the most prevalent non-communicable diseases worldwide, such as metabolic syndrome, diabetes mellitus, cardiovascular diseases and cancer, underlie the activation of inflammatory mechanisms, which can compromise immune functions, often caused or accompanied by alterations in nutritional patterns and intestinal microbiota. In this context, it is clear that diet is a key modulator of the immune system and much interest is emerging in the area of nutrition as a means of treatment and prevention. The Mediterranean diet has been widely described as positively influencing and is proposed not only as a potential tool in the clinical management of different diseases, but also for global health promotion. Therefore, the aim of this review is to address the current knowledge on the regulatory role of the nutritional components present in the Mediterranean diet on the immune system and the intestinal microbiota.